SANITATION AND DETOXIFICATION OF LAMA MEAT (LAMA GLAMA) INFECTED WITH SARCOCYSTIS AUCHENIAE THROUGH BOILING, BAKING, FRYING AND FREEZING - Godoy Z., Roxana (2007)
The aim of the study was the sanitation and disinfecting llama meat naturally infected with macrocysts of Sarcocystis aucheniae through any of four physical methods: boiling (100 ºC for 10 min), baking (105 ºC for 65 min), frying and freezing (-20 ºC for 10 days). A lisis of macrocysts from treated and non-treated meats was prepared and inoculated (100 μg/kg of body weight, subcutaneously).into 30 rabbits of 4-5 months of age. Only rabbits of the positive control group (non-treated meat) died. Rabbits of the frozen meat group showed moderate toxicity signs. Furthermore, 13 puppies (2-5 months of age) were fed with 200 g of treated or non-treated infected llama meat. Puppies of meat-treated groups did not eliminate sporocysts in the feces as compared to puppies of the non-treated meat that had sporocysts after 14 days of the feeding. It can be concluded that boiling, baking, and frying (and freezing in some extent) cleaned and disinfected the toxin in the macrocysts of S. aucheniae and all four methods affected cysts viability.